The Influence of Shipyard Layout on Sustainability Performance Based on the Triple Bottom Line through Operational Efficiency Mediation: A SEM-PLS Approach - Didik Hardianto; Marjono Marjono; Anthon Efani; Andi Kurniawan (International Journal of Marine Engineering Innovation and Research, 2026)
This study examines the effect of shipyard layout on sustainability performance based on the Triple Bottom Line, with operational efficiency as a mediator. The main issue is a layout that evolves without integrated planning, reducing material flow efficiency and operational performance. The method used is Structural Equation Modeling–Partial Least Squares (SEM-PLS) based on questionnaire data with purposive sampling. The results indicate that layout has a significant effect on sustainability performance, both directly and through operational efficiency as a key mediator. These findings confirm that layout optimization not only enhances efficiency but also improves environmental and social performance. This study positions layout as a strategic determinant in a sustainable production system.